An Irritation Test of Optimum Preparation of Celery Extract Face Clay Cleanser With Sodium Lauryl Sulfate (SLS) and Cocamidopropyl Betaine (CAPB) as Surfactants: Irritation Test of Optimum Preparation of Celery Extract Face Clay Cleanser With Sodium Lauryl Sulfate (SLS) and Cocamidopropyl Betaine (CAPB) as Surfactants - Bunga Eloystina, Laurencia Julia; Aldila, Silvy; Girsang, Valentina; Sa'adah, Anifatus (Science and Community Pharmacy Journal, 2024)
Surfactant is one of the important things in making face clay cleanser preparations. Sodium Lauryl Sulfate (SLS) is an anionic type surfactant that is often used in cosmetic products. The use of Sodium Lauryl Sulfate (SLS) can cause irritation and dry skin. Combination with cocamidopropyl betaine (CAPB) which is amophoteric can reduce skin irritation. Based on this, a safety test is needed which aims to meet the preparation requirements before being marketed to the wider community. One of the safety tests that can be done is the skin irritation test. The test method used is the human patch test. The irritation test of the optimum preparation of face clay cleanser celery herb extract (Apium graviolens L.) with a concentration of 0.5% SLS and 9.5% CAPB was carried out on 6 volunteers consisting of men and women aged 20-35 years, the score of the degree of irritation was 0, which means that the preparation is not irritating. Based on the evaluation with SPSS, it can be concluded that there is no significant difference (p>0.05) for the irritation test results and the optimum preparation of celery herb extract face clay cleanser (Apium graviolens L.) meets the safety requirements.